THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH INFORMATION TECHNOLOGY ADOPTION AS A MODERATING VARIABLE - Ary Aditya; Sambung Roby; Jonathan Giovanni (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective –  This research aims to examine the influence of transformational leadership and work motivation on employee performance with information technology's role as a moderating variable. Design/Methodology/Approach –  The research employs a quantitative analysis method, utilizing non-probability sampling with a saturated sampling method (census) where the entire population is sampled, totalling 49 respondents. The analysis technique used is Smart Partial Least Square version 4.1. Findings – The results of the study indicate that transformational leadership has a positive and significant impact on employee performance, work motivation has a positive and significant effect on employee performance, the role of information technology has a negative and non-significant moderating effect on the influence of transformational leadership on employee performance, and the role of information technology has a positive and significant moderating effect on the influence of work motivation on employee performance. Conclusion and Implications – The transformational leadership and motivation positively influence employee performance. The role of technology adoption as a moderating variable can only affect to relationship between transformational leadership and employee performance. Moreover, for future research, it is suggested to make information technology's role an independent variable directly affecting employee performance.